Cultural Contents in MyEnglishStep Digital Learning Materials for Junior High School Students - Maulidya, Alga Dilfa Suci; Palupi, Tara Mustikaning; Agustina, Imas Wahyu (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2023)
The present research aimed to analyze the cultural contents available in digital learning materials for Junior High School Students called myenglishstep.com. The data were analyzed using qualitative content analysis under two frameworks, particularly the cultural categories framework by Chao (2011) and the framework of the cultural dimensions by Moran (2001). The results revealed 1.472 cultural contents, covering all five cultural categories: Source Culture, Target Culture, International Culture, Intercultural Interaction, and Universality across Cultures. Further, the cultural contents are also represented through Cultural Dimensions, namely Products Dimension, Practices Dimension, Perspectives Dimension, Communities Dimension, and Person Dimension. The cultural contents mainly appeared as much as 1160 times in the Universality across Cultures and were presented through products created and invented by the social communities approximately 623 times. These results, to some extent, show that material developers are aware of the importance of cultural content to cater to diversity in Indonesia.